Self‐Assembled 1D‐Nanowire Lasers of Perylenediimides. Issue 20 (24th August 2016) - Yu, Zhenyi; Wu, Yishi; Zhang, Haihua; Wang, Xuedong; Chen, Jianwei; Yao, Jiannian; Fu, Hongbing
Abstract: The 1D nanostructures of perylenediimides (PDIs) have been readily obtained owing to strong cofacial π–π stacking interactions, which, however, subsequently render PDIs weakly emissive in the solid state. Therefore, organic solid‐state lasers based on 1D nanostructures of PDIs have not been achieved yet. Herein, we prepared 1D‐nanowires of N, N'‐bis(1‐ethylpropyl)‐2, 5, 8, 11‐tetrakis( o ‐methylphenyl)‐perylene‐3, 4:9, 10‐tetracarboxylic acid diimide (mp‐PDI), which stack into a loosely J‐type arrangement. J‐aggregation leads to a solid‐state photoluminescence (PL) efficiency φ >18 % and the nanowires of mp‐PDI exhibit excellent Fabry–Perot (FP) mode laser action. Abstract : Laser wires : The preparation of nanowires of a perylene diimide compound stacking into emissive J‐aggregates is presented. These nanowires exhibit excellent Fabry–Perot (FP) mode laser action.